PERANCANGAN SISTEM INFORMASI INVENTARIS DENGAN LABEL BARCODE BERBASIS WEB PADA SMK MUHAMMADIYAH 3 WELERI - Mudrofi Mudrofi; Bagus Sudirman; Ahmad Ashifudin Aqham; Miftahurrohman Miftahurrohman; Moh Muthohir (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
The management of data and information plays a crucial role in supporting the effectiveness of an institution's operational activities. An essential component of this management is inventory administration, which serves to control, monitor, and utilize assets to facilitate operational tasks. Therefore, institutions are required to implement systematic inventory management aligned with their operational objectives. In practice, however, many institutions have not fully optimized their inventory systems. SMK Muhammadiyah 3 Weleri, for instance, still faces several challenges in managing inventory. These challenges primarily arise from the reliance on manual procedures throughout inventory activities. Inventory records are maintained using notebooks and subsequently summarized in ledgers. This manual approach often results in incomplete, damaged, or inconsistent records, particularly in tracking borrowed items. Consequently, information regarding item availability becomes less accurate, leading to inefficiencies in preparing practical equipment.